Does genius border on insanity? Part I: A relationship between creativity and the presence of psychopathological symptoms in bipolar disorder - Nowacka, Olga; Welcz, Henryk; Karakuła-Juchnowicz, Hanna (Current Problems of Psychiatry, 2017)
The theory linking the development of mental disorders with the processes of human evolution assumes that these disorders may be the result of a side effect of natural and sexual selection processes. Creativity is one of the adaptive features associated with the increased incidence of psychopathological symptoms (as compared to the general population). In this review paper, the definition of creativity has been characterized, and contemporary existing theories on its background, have been presented. Also, the paper describes the relationship between creativity and the presence of psychopathological symptoms. Special attention has been paid to the relationship between creativity and bipolar disorder. The research results prove the existence of a correlation between a high level of creativity and a higher prevalence of psycho-pathological symptoms, particularly concerning the symptoms of bipolar disorder spectrum.